1999
DOI: 10.1021/cr980420v
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Platinum-Based Antitumor Drugs

Abstract: Industrial Research Fellow, investigating the coordination of technetium and rhenium to peptides and the synthesis of low molecular weight radiopharmaceuticals. His research interests centered on the applications of technetium and rhenium radiopharmaceuticals to oncology and neurology. In 1998, he joined the platinum development team at AnorMed, Inc., as a Senior Developmental Scientist. His current research interests include the design and synthesis of new Pt antitumor agents and the design of efficient proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
1,347
0
19

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,786 publications
(1,379 citation statements)
references
References 164 publications
13
1,347
0
19
Order By: Relevance
“…These crucial factors are responsible for treatment failure. 25 Derivatives of 3a-aza-cyclopenta [-]indene (BO-1090, -1100, -1130 and -1131) were rationally designed to have increased affinity and specificity toward the DNA in cancer cells. We have shown that these 3a-aza-cyclopenta[a]indene derivatives are effective against the growth of different cancer cells in xenografted mice.…”
Section: Discussionmentioning
confidence: 99%
“…These crucial factors are responsible for treatment failure. 25 Derivatives of 3a-aza-cyclopenta [-]indene (BO-1090, -1100, -1130 and -1131) were rationally designed to have increased affinity and specificity toward the DNA in cancer cells. We have shown that these 3a-aza-cyclopenta[a]indene derivatives are effective against the growth of different cancer cells in xenografted mice.…”
Section: Discussionmentioning
confidence: 99%
“…Native DNA (calf thymus) gave CD bands at~248 nm (negative) arising due to B-form right-handed helicity, and~270 nm (positive) originating from uniform nucleobase stacking in the B-form conformation. [21] When the free ligands L 1 and L 2 and the platinum complexes [PtL 1 Cl 2 ] and [PtL 2 Cl 2 ] were allowed to interact with DNA, prominent changes were observed in helical conformation, indicative of strong binding of the compounds to DNA. (Figure 3).…”
Section: Analysis Of Dna Conformational Changes By Circular Dichroismmentioning
confidence: 99%
“…[1] Among several platinum-containing candidates, cisplatin, carboplatin, and oxaliplatin have been approved for clinical use. [2] Investigation into the activity of cisplatin at the biomolecular level indicates that genomic DNA is the primary target, where cisplatin forms an adduct with adjascent purine bases, [3] particularly with guanine.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallographic data is shown in Table 1 with selected bond lengths shown in Table 2. The sulfur atom S(1) and the azomethine nitrogen atom N(3) are in trans position with respect to the C(2)-N(2) bond and the same configuration is observed for S (2) and N(7) with respect to 5 the C(9)-N(8) bond, therefore the ligand exists in E configuration which is often observed in thiosemicarbazones. 27 The azomethine bond distances of 1.288(3) and 1.290(2) are in conformity with a formal C=N double bond and the C-S bond distances of 1.678 (2) and 1.684(2) Å , are very close to a formal C=S double bond 10 length, these facts confirm the existence of the thiosemicarbazone groups in the thione form, in the solid state.…”
Section: Description Of the Crystal Structuresmentioning
confidence: 52%
“…For comparison purposes the toxicity of cisplatin was evaluated under the same experimental conditions. 2 7 ± 3 > 100 Cisplatin 92 ± 1 7.03 ± 0.08…”
Section: Nephrotoxicitymentioning
confidence: 99%